The meaning of speaker according kmal aldeen den ali al- behrany (Journal of Imam Al-Kadhim College, 2023)
AbstractThis paper aims to contemplate the mechanisms and means used by Sheikh Maytham Al-Bahrani in his book (Explanation of Nahj Al-Balaghah) to reveal and deduce the purposes of Imam Ali (peace be upon him), and to compare those inferences with what was produced by the project of the American philosopher (Paul Grice), who is one of the most important contributors to the study The meaning in the modern Western lesson, and the focus will be on the concept (Speaker's meaning) and what is related to it, especially the principle of cooperation and the rules that govern dialogue, and the meanings that are generated when those rules are violated. I believe that this approach and others like it contribute to presenting a new reading of our linguistic heritage, in addition to enabling us to assess the value of that heritage, which contains the roots of most modern linguistic theories.
Keywords: meaning, speaker,dialogue,Maytham,Bahrani,Grace